Malaysian communication and multimedia commission: A model of united communications regultor for Hong Kong - Zul Kepli, Mohd Yazid; Wu, Richard (LexisNexis, 2010)
In mature economies, the phenomenon of technological convergence results in users having access to same communications services through multiple media and increases competition in the communications industries and in developing countries, convergence enhances the penetration of communications services. Given this ongoing development on technological convergence, many countries have adopted a unified communications regulator to cope with the convergence phenomenon on the ground that such a regulator will better adapt to technological convergence and market changes by providing a comprehensive and coherent regulator approach, improving regulatory clarity and certainty, and avoiding inefficiencies resulted from jurisdictional overlaps of multiple regulators. In Asia, Malaysia established the first unified regulator called Suruhanjaya Komunikasi dan Multimedia Malaysia, which is also known as Malaysian Communication and Multimedia Commission (MCMC) in the late 1990s. In 2006, the Hong Kong government also issued a consultation paper on the establishment of a unified communications regulator called the Communications Authority. As Malaysia is the first Asian country to adopt a unified communications regulator, the implementation experience of MCMC should provide invaluable lessons for other jurisdictions in Asia like Hong Kong that desire to establish such a regulator. In this paper, the authors study the Malaysian experience and its relevance to Hong Kong. They first give an overview of the regulatory reforms in the Malaysian communications sectors, before analyzing the implementation experience of MCMC. In the second part of this paper, they examine the policy goals of Hong Kong government for establishing a unified regulator, and argue that Hong Kong can learn many lessons from the Malaysian experience if it proceeds to establish the Communications Authority. For example, such a regulator cannot be effective with bureaucracy and should be independent. Appointment of credible and competent persons is also crucial to the success of such a regulator. The regulator should adopt a light-hand approach in regulating the communications sectors. Adequate funding is also crucial to the success of such a regulator, and finally, adequate legislation and regulation is necessary both for its adoption and implementation.